2019
DOI: 10.3390/ijerph16183463
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of the Rational Antibiotic Use System on Hospital Performance: The Direct Effect and the Spillover Effect

Abstract: Irrational antibiotic usage not only causes an increase in antibiotic-borne diseases, but also inflicts pain on patients, as a result of inappropriate treatment. In order to resolve the hazards caused by irrational antibiotic usage, a kind of e-health service, the Rational Antibiotic Use System (RAUS), has been incorporated into the hospital information system. The RAUS provides doctors and patients with the functions of antibiotic usage monitoring, antibiotic information consultation and antibiotic prescripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…These disparities are mainly due to variation in site and time of the studies while few are due to differences in the detection method. Most of the studies used phenotypic detection methods and also emphasized the need for routine reporting of these common MDROs to guide in rational use of antimicrobials and for good antimicrobial stewardship that will ensure patient safety (18,19). Association of both MRSA and inducible clindamycin resistance with individual resistance to erythromycin and clindamycin as observed in this study is similarly reported by several other studies in Nigeria and other countries (5, 9-11, 17, 20).…”
Section: Discussionsupporting
confidence: 81%
“…These disparities are mainly due to variation in site and time of the studies while few are due to differences in the detection method. Most of the studies used phenotypic detection methods and also emphasized the need for routine reporting of these common MDROs to guide in rational use of antimicrobials and for good antimicrobial stewardship that will ensure patient safety (18,19). Association of both MRSA and inducible clindamycin resistance with individual resistance to erythromycin and clindamycin as observed in this study is similarly reported by several other studies in Nigeria and other countries (5, 9-11, 17, 20).…”
Section: Discussionsupporting
confidence: 81%
“…The criterion for starred SDHs standard is an effective strategy for the development of primary care prescribing in the community [ 25 ]. In addition, evidence shows that implementing the RDU campaign could effectively improve rational antibiotic prescribing in primary care and hospital in both short- and long-term maintenance [ 26 , 27 ], whereas the reward plays a motivational role to support and urge workers to produce a good performance and high-quality work [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%